TRANSLATION OF PRAGMATIC MARKERS IN LITERARY TEXTS - Khasanova Dilnoza (PEDAGOGS, 2025)
Abstract. Pragmatic markers (PMs) — also known as discourse markers — play a subtle yet significant role in shaping meaning, coherence, speaker attitude, and interactional tone in spoken and written discourse. Their presence in literary texts, especially in dialogue and character development, is crucial to maintaining the stylistic, cultural, and communicative authenticity of the source. However, translating pragmatic markers poses considerable challenges due to their context-dependent meanings, multifunctionality, and culture-specific use. This article explores the nature of pragmatic markers, their narrative functions in literature, and the difficulties of preserving them in translation. It also examines strategies translators can employ to render these elements effectively and provides illustrative examples across language pairs.